2014
DOI: 10.1002/ece3.1321
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveals novel insights into pterygophagy and prey selection in distichodontid fishes (Characiformes: Distichodontidae)

Abstract: DNA barcoding was used to investigate dietary habits and prey selection in members of the African-endemic family Distichodontidae noteworthy for displaying highly specialized ectoparasitic fin-eating behaviors (pterygophagy). Fin fragments recovered from the stomachs of representatives of three putatively pterygophagous distichodontid genera (Phago, Eugnathichthys, and Ichthyborus) were sequenced for the mitochondrial gene co1. DNA barcodes (co1 sequences) were then used to identify prey items in order to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…DNA barcoding was conducted using COI sequences blasted in the GenBank and BOLD online databases with a threshold of similarity higher than 98% [42]. Specimens would be re-examined if any conflict exists between morphological and molecular identification.…”
Section: Methodsmentioning
confidence: 99%
“…DNA barcoding was conducted using COI sequences blasted in the GenBank and BOLD online databases with a threshold of similarity higher than 98% [42]. Specimens would be re-examined if any conflict exists between morphological and molecular identification.…”
Section: Methodsmentioning
confidence: 99%
“…g . fish fillets and caviar), stomach contents as well as fish larvae and eggs (Desalle & Amato, ; Carreon‐Martinez et al , ; Carvalho et al , 2011 a ; Ko et al , ; Arroyave & Stiassny, ; Loh et al , ). For instance, Loh et al () developed and applied DNA barcoding to identify 14 of the 16 species inhabiting the Brisbane River (Australia), including a quantitative (q)PCR assay for species‐specific detection and quantification.…”
Section: Introductionmentioning
confidence: 99%
“…This observation reinforces the idea that more sequences of fish species must be deposited in databases, especially in river basins with rich fish fauna as the Upper Paraná River. Another positive aspect is that, compared with DNA barcoding (Arroyave and Stiassny 2014, Becker et al 2015, Frantine-Silva et al 2015, our method can trigger significant advances in the quality of ecological studies in fish, as observed in some recent studies with metabarcoding (Guillerault et al 2017, Maggia et al 2017, Mariac et al 2018, Barbato et al 2019 and, mainly, to ensure significant reduction in labor time and cost per specimen reaching 80% of reduction (Shokralla et al 2015). Despite some differences in obtaining DNA samples, both environmental DNA (eDNA) and DNA metabarcoding from bulk samples are subject to false negatives and false positives (Ficetola Gentile et al 2015Gentile et al , 2016Divoll et al 2018).…”
Section: Species Identificationmentioning
confidence: 99%